(untitled) (Proceedings of the YSU B: Chemical and Biological Sciences, 2005)
The article gives facts about forage crops’ dangerous fungal diseases, which are more spread in Armenia. Are pointed more dangerous types of fungi, which are adapted to those plants’ certain genera, are pointed out steady tips to pathogens.